摩托车振动系统建模及仿真 - 邹喜红; 石晓辉; 施全; 肖顺利 (Jixie chuandong)
The vibration performance of motorcycle effects not only ride comfort,but also security.The five DOF vibration model of motorcycle is built,and the differential equation of motion is developed according to Lagrange equation.By selecting appropriate state variable,the state-space formulation is obtained.At last,the system is simulated with Matlab.As a result,the analysis and design method is developed.